Michael K’s Zoological Life in Coetzee’s Life and Times of Michael K: An Agmbenian Insight - Sharma, Pradip (Literary Studies, 2023)
This paper explores Michael K’s zoomorphic life in The Life and Times of Michael K. Zeroing in on J.M. Coetzee’s novel, I argue that K’s relegation to creaturely life permeated by the colonial regime substantiates Giorgio Agamben’s ‘bare life,’ life subjected to suffering and injustice. K, a socially excluded man suffers in riot run Cape Town. His preference to cave life verifies his zoological life which sharply ridicules Foucauldian claim of life proliferating biopolitical governmentality. Rather the socio-political injustice K witnesses problematizes Agamben’s analytics of homo sacer, a liminal human figure pushed away from the socio-political security. Thus, linking the liminal life of K with homo sacer, this article examines his animalized life (zoé) when he witnesses the ripping off his political life (biós) during the civil war. The declaration of emergency, intimidation, and forced labor camp exercised by the state offers him docile and bestialized life undistinguished from biós and zoé. This article discusses on how overarching biosovereign power subjects K to embody precarity and outlawry that begets him a bare life. Finally, it creates an academic avenue in Life and Times of Michael K to make a biopolitical discourse in humanities.